RESTORATIVE JUSTICE APPROACHES FOR CRIMES AGAINST WOMEN IN INDIA ASSESSING THE POTENTIAL OF ALTERNATIVE DISPUTE RESOLUTION MECHANISMS IN ACHIEVING JUSTICE AND REHABILITATION. - Victoria, A. Lilly; B. Venugopal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article delves into the utilization of restorative justice strategies to confront crimes against women in the distinctive socio-legal milieu of India. With a central focus on evaluating the viability of alternative dispute resolution mechanisms, the study meticulously examines the intricate interplay of cultural and legal factors influencing the execution of restorative justice. By exploring the unique complexities within the Indian context, the research aims to shed light on the potential of these approaches in fostering justice and rehabilitation for both survivors and offenders. Through a comprehensive analysis, the article seeks to unravel the effectiveness of restorative justice in navigating the intricacies of the Indian legal landscape, contributing valuable insights to the on-going discourse on enhancing the criminal justice system's responsiveness to crimes against women in the region.